A Re-emergence of Subacute Sclerosing Panencephalitis in the United Kingdom. Issue 1 (12th October 2022) - Campbell, Helen; Lopez Bernal, Jamie; Bukasa, Antoaneta; Andrews, Nick; Baker, Elaine; Maunder, Polly; Winstone, Anne Marie; Ramsay, Mary; Verity, Christopher; Brown, Kevin
Abstract : New pediatric and adult subacute sclerosing panencephalitis cases between 1996 and 2020 were reported based on an established UK registry with no evidence of under-ascertainment using a separate pediatric surveillance system. After 15 years with no pediatric UK-acquired cases, 3 cases arose from 2017 after increased measles. Modeling suggested this was in line with measles notifications, underreporting of laboratory-confirmed measles or increased subacute sclerosing panencephalitis risk.